Evaluation on the effect of scientific research training for postgraduates of reproductive medicine before entering the laboratory - LONG Xiaoyu; QIAO Jie; ZHU Xiaohui (Yixue xinzhi zazhi)
Objective To understand the perceptions and needs of graduate students and postdoctoral researchers at the Key Laboratory of Assisted Reproductive of Peking University Third Hospital (PUTH) regarding pre-laboratory scientific research training, and to provide suggestions for enhancing the research capabilities of graduate students and postdoctoral researchers in reproductive medicine.Methods An anonymous questionnaire survey was employed, with content covering cognitive understanding of training, specific needs, effectiveness evaluations, and suggestions for improvement.Results A total of 55 students participated in the survey, including 17 postdoctoral fellows (30.91%), 25 doctoral fellows (45.45%), and 13 eight-year students and master's degree students (23.64%). 21.82% of the students had never been involved in scientific research work, while 78.18% had some research experience. All students expressed satisfaction with the training arrangement, but 40.00% of students hoped to extend the teaching time, 60.00% hoped to increase the teaching content, 23.64% hoped to increase online teaching, and 21.82% hoped to increase reproductive clinical internships. In terms of training effectiveness, research-oriented and research-experienced students had higher ratings of research ability, improvement of research thinking and course satisfaction than clinical-oriented and non-research-experienced students. Eight-year students and postdoctoral fellows had higher ratings of research thinking, practical application and satisfaction with the course than master's and doctoral fellows, but there were no significant differences (P>0.05).Conclusion Pre-laboratory scientific research training has a positive impact on enhancing the abilities of graduate students and postdoctoral researchers in reproductive medicine. However, improvements are needed in the training mechanism. Efforts should be made to optimize training content and methods, increase opportunities for practical operations, strengthen teacher-student interaction and feedback mechanisms, and improve the relevance and effectiveness of training. Additionally, an objective evaluation system for training effectiveness should be refined to emphasize the development of innovative thinking and research capabilities, thereby supporting the cultivation of highly skilled talents in reproductive medicine.